Legal Protection of Patient’s Electronic Medical Record: Indonesian Legal Perspective - Basani, Christin Septina (Dialogia Iuridica, 2023)
Health is the most fundamental factor of every citizen, particularly in Indonesia. Considering that many people need health services, patients’ data are pivotal as they contain patients’ health and medical records, identity, examination, medication, and other services patients receive in health services. Medical record in Indonesia is regulated by the Minister of Health Regulation No. 269 of 2008 on Medical Record and the Minister of Health Regulation No .22 of 2022 on Electronic Medical Record. The transition to electronic medical records is expected to finish on 31 December 2023. Electronic Medical Records (EMRs), which are now being implemented across the healthcare system in Indonesia, have the potential to fulfill the rights of citizens in the healthcare sector. On the other hand, data security for patients requires protection, as electronic systems may be vulnerable to data breaches and misuse by unauthorized individuals. The objective of this research is to examine the legal protection for patients when their electronic medical record data is misused and to elucidate patients’ rights in the realm of healthcare, particularly concerning medical records. The research employs a normative juridical approach with a legislative regulation focus. Article 29 of Minister of Health Regulation No. 22 of 2022 already addresses data protection for patients’ personal information, although continuous monitoring of the implementation of patient’s Electronic Medical Records is still necessary. The findings of this study emphasize the necessity of ensuring data protection guarantees for patients stored within electronic systems.